Stang’s Law in Baltic, Greek and Indo-Iranian - Pronk, Tijmen (Baltistica, 2016)
The article discusses the development of the Proto-Indo-European sequences *-eum and *-eh2m. The former produced *-ēm, allegedly through loss of *-u- with compensatory lengthening of the preceding *-e- (“Stang’s law”), while *-eh2m allegedly produced *-ām within the proto-language (“extended Stang’s law”). The evidence for both claims is scrutinized, with special emphasis on the acc.sg. and acc.pl. endings of the ā-stems in Indo-Iranian and Baltic and the Proto-Indo-European paradigm of the word for ‘cow’. It is concluded that “extended Stang’s law” cannot be maintained and that “Stang’s law” is probably inorrect, too. Alternative explanations for the attested forms are given.